Impact of Cytomegalovirus Infection on the Outcome of Patients With Cirrhosis: A Preliminary Study. Issue 3 (March 2019) - Faivre, Morgan; Cottet, Vanessa; Bour, Jean-Baptiste; Richou, Carine; Valmary-Degano, Séverine; Thiefin, Gerard; Andreoletti, Laurent; Geist, Claire; Schvoerer, Evelyne; Malvé, Brice; Habersetzer, François; Fafi-Kremer, Samira; et al.
Abstract : Goals: The aims of this study were to evaluate whether cytomegalovirus (CMV) infection is associated with hepatocellular carcinoma (HCC) and liver-related mortality in cirrhotic patients. Background: In cirrhotic patients, the determinants of HCC and liver-related death are imperfectly known. CMV infection, by its prooncogenic and proinflammatory properties, may favor both the development of HCC and deleterious systemic inflammation. Study: In the 1178 patients included between June 2008 and December 2012 in the CIrrhose et Risque de Carcinome Hépatocellulaire dans le grand-Est (CIRCE) study, a French multicenter case-control study designed to identify risk factors of HCC among cirrhotic patients, we identified 432 patients with interpretable CMV serological status at baseline. They included 159 cases with HCC and 273 controls. We measured factors associated with HCC at baseline and subsequent HCC in controls, and predictors of overall and liver-related death in the whole study population. Results: During a median follow-up of 31 months, 25 cases of HCC developed in controls, and 209 deaths (163 liver-related) were recorded. There were 247 (57.2%) CMV-seropositive patients. CMV seropositivity was not associated with more frequent HCC at baseline or during follow-up, but among CMV-positive patients with HCC, the proportion of multinodular, infiltrative, or metastatic tumors at diagnosis was higher (73.8% vs. 57.3%; P =0.029), inducing higher mortality (74% vs. 52% at 3 years; P =0.004). By Cox-regression adjusted for age, gender, Model for End-stage Liver Disease (MELD) score, HCC at baseline, and diabetes, CMV seropositivity independently predicted all-cause (hazard ratio=1.45; 95% confidence interval, 1.08-1.94; P =0.013) and liver-related mortality (hazard ratio=1.56; 95% confidence interval, 1.04-2.30; P =0.031). Conclusions: In this preliminary study, CMV-seropositive cirrhotic patients were at higher risk of liver-related death caused by more aggressive HCCs or severe cirrhosis complications. These findings warrant confirmation.